Effectiveness Of Productive Zakat Management In Livestock Business Development: Study on Mustahik in Rukti Endah, Central Lampung - Wijayanti, Fitri; Ranny Priyatna, Aulia (Nuban Jagadhita Centre, 2023)
Purpose: This study aims to determine the effectiveness of productive zakat management in the development of the mustahik livestock business. Methodology: The type of research conducted is field research, namely research conducted at research locations. The nature of this research is descriptive qualitative, namely a method used to answer research problems originating from interviews, observations, and excavation of documentation. The source of data consists of primary and secondary data. The data collection techniques used were interviews and documentation with Central Lampung BAZNAS management, the Head of the Animal Husbandry Center, and the Head of the livestock group, Muzaki, and Mustahik. Findings: Based on this research, the allocation of productive zakat funds was carried out in four villages from 1 sub-district which were divided into 4 groups of 45 people. This effectiveness is inseparable from the intervention of BAZNAS in implementing the planned procedures from planning to supervision. Mustahik was given livestock business capital in the form of 5 heads, consisting of 1 female goat and 4 male goats of the Boer type, of which 3 male goats will be exchanged for female goats. In addition, livestock manure management is also used for fertilizer and holding organic farms to make it easier for farmers to find feed.